Evolution of Tariff Government Regulation in Energy and Communal Markets on the Basis of Smart Regulation System - N. V. Popov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The Aim. Analysis of eﬀects according to digital pricing system advent in energy and communal sphere in Russia as a part of new industrial revolution.Purpose of a research. Review of a current world trends on energy markets, determination of ways and instruments for tariﬀ regulation digital development on the energy and communal markets, deﬁnition of possible results from complex digitalization of tariﬀ regulation system.Methodology of a research. During research of this article were widely applied instruments of complex theoretical analysis, cause-eﬀect relations were tested between theoretical hypothesis and practical realization of digital tariﬀ regulation models.Result of a research. By the author were written and systematic deﬁned concept of pricing digitalization system on the Russian energy and communal markets according to analysis of main world trends in this economic sphere. The term of digital platform of tariﬀ regulation was developed.Output. Digitalization of tariﬀ regulation could develop premises for deregulation of energy and communal spheres in Russia enable the competence development and lower the entrance barriers for new market players what can lead to higher innovation and investment level recruited in these important markets.